Substituent effect on corrosion inhibition of Schiff bases derived from isatin / Aliyin Abdul Ghani … [et al.] - Abdul Ghani, Aliyin; Bahron, Hadariah; Hj Harun, Mohamad Kamal; Kassim, Karimah (Penerbit UiTM (UiTM Press), 2016)
Two Schiff bases, 3-(4-hydroxyphenylimino)-l,3-dihydroindol-2-one (OPI) and 3-(4-Chloro-phenylimino)-l,3-dihydroindol-2-one (CPI) were successfully synthesized through condensation reactions giving yields of 82% and 63%, respectively. The compounds were characterized via physical and spectroscopic techniques, namely elemental analysis (C, H,N), ], ¹H and ¹³C Nuclear Magnetic Resonance (NMR) spectroscopy, Fourier Transform Infrared (FTIR) spectroscopy and melting point. The corrosion inhibiting property of the Schiff bases on mild steel in 1 M HC1 solution was investigated by the weight loss (WL) measurements, electrochemical impedance spectroscopy (EIS) and linear polarization resistance (LPR). The concentrations of the Schiff bases were varied from 1 x 10⁻³ M to 1 x 10⁻⁵ M. The inhibition efficiencies obtained from all the methods employed were in good agreement where the percentage of inhibition efficiencies increased with concentration. OPI showed better inhibition efficiency than CPI with 91% highest inhibition efficiency at 1 x 10⁻³ M additive concentration. This is likely to be caused by the resonance donating effect due to the presence of the hydroxyl group. The adsorption behaviour obeyed Langmuir isotherm for monolayer formation.